Installed Base as a Facilitator for User-Driven Innovation: How Can User Innovation Challenge Existing Institutional Barriers? - Synnøve Thomassen Andersen; Arild Jansen (International Journal of Telemedicine and Applications)
The paper addresses an ICT-based, user-driven innovation process in the health sector in rural areas in Norway. The empirical base is the introduction of a new model for psychiatric health provision. This model is supported by a technical solution based on mobile phones that is aimed to help the communication between professional health personnel and patients. This innovation was made possible through the use of standard mobile technology rather than more sophisticated systems. The users were heavily involved in the development work. Our analysis shows that by thinking simple and small-scale solutions, including to take the user’s needs and premises as a point of departure rather than focusing on advanced technology, the implementation process was made possible. We show that by combining theory on information infrastructures, user-oriented system development, and innovation in a three-layered analytical framework, we can explain the interrelationship between technical, organizational, and health professional factors that made this innovation a success.